Penyuluhan Hidup Sehat Tanpa Rokok: Penyuluhan Hidup Sehat Tanpa Rokok - Maidartati, Maidartati; Iklima, Nurul; Tania, Mery; Saputra, Anggi; Khasanah, Umi (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Smoking is the act of inhaling and drawing in tobacco smoke, which contains harmful substances such as nicotine, carbon monoxide, and tar, and can lead to various health problems. The aim of this activity is to provide counseling on healthy living without smoking. This counseling session was held on July 31, 2024, at SMP PGRI Mekar Manik, with participants being students from grades VII, VIII, and IX. The methods used in this counseling included distributing leaflets and showing a video on the effects of smoking on the body's organs. The leaflets provided information on the definition of smoking, the substances contained in cigarettes, the health side effects of smoking, ways to reduce smoking addiction, and the benefits of not smoking.